Avaliação da qualidade fisiológica e sanitária de sementes de abóbora variedade menina brasileira - Casaroli, Derblai (2005)
Knowing the importance of to evaluate the physiological and health quality of the seeds, this present work objectived to determine the exposition period of the seeds at shortest temperature in the cold test and the temperature and the aging period in the accelerated aging test and to compare vigour tests to determination of the physiological potential of seeds. To evaluate the health quality and the correlation her with the physiological quality of squash seeds objectived too. Two seed lots of squash, variety Menina Brasileira (Cucurbita moschata Duch.), produced in the agroecological system and four lots produced in the conventional system, with chemical treatment or without, were evaluated. In the chapter I, studying the cold test, with exposition periods three, five, seven and nine days at to 10 °C of constant temperature were evaluated. In the accelerated aging test, were studied the temperature of 41 °C and 44 °C for aging periods of 24, 48 and 72 hours. Was detemined the umidity degree of the seeds, before and after the accelerated aging. For the comparation between tratments, in the two tests studied, was determined the germination and the vigour (first count, germination speed index and seedling emergence tests) of the lots. The exposition period of five days at shortest temperature was the best to the cold test and 41 °C and 48 hours were the conditions more adequate for the accelerated aging test. In the chapter II, were compared the germination first count, germination speed index, cool germination, accelerated aging, seedling emergence at to seven, 14 and 21 days after sowing, emergence speed index, dry biomass partial and total of seedlings evaluated at to six days after sowing and dry biomass partial and total of plants evaluated at to 21 days after sowing. The results indicated that the germination first count, accelerated aging, dry biomass of root, stem, root and stem, and leafs of plants evalueted at to 21 days after sawing, were prudents the more efficiente tests to evaluate the physiological potential of the squash seeds. In the chapter III, the seed lots were submitted to health tests, following methodology of Blotter test freezing, correlating with the germination and vigour (obtained in the chapter I and II). The fungal Fusarium spp., Alternaria spp., Rhizopus spp., Penicillium spp., Cladosporium spp. and Phoma spp were detached associated with seeds. Dead seeds were not found despite incidence of fungal. The fungal incidence not interfered of significative form in the physiological quality of squash seeds.